Emotional Modulation of the Synapse - Christa McIntyre (Frontiers Research Topics, 2015)
Highly emotional events tend to be well remembered. The adaptive value in this is clear - those events that have a bearing on survival should be stored for future use as long-term memories whereas memories of inconsequential events would not as likely contribute to future survival. Enduring changes in the structure and function of synapses, neural circuitry, and ultimately behavior, can be modulated by highly aversive or rewarding experiences. In the last decade, the convergence of cellular, molecular, and systems neuroscience has produced new insights into the biological mechanisms that determine whether a memory will be stored for the long-term or lost forever. This Research Topic brings together leading experts, who work at multiple levels of analysis, to reveal recent discoveries and concepts regarding the synaptic mechanisms of consolidation and extinction of emotionally arousing memories.